Pengaruh model pembelajaran Learning Cycle 7E terhadap hasil belajar kognitif fisika siswa kelas X SMAN 3 Rambah Hilir - Rohani, Siti; Hatika, Rindi Genesa; Rita, Silvia (Karoteh Utama, 2020)
This study examines the influence of the Learning Cycle 7E instructional model on the cognitive learning outcomes of Physics students in Class X of SMAN 3 Rambah Hilir. This research is a pre-experimental study with a quantitative descriptive approach using a One-Group Pretest-Posttest design. The study was conducted in Class X-2 of SMAN 3 Rambah Hilir, focusing on temperature and heat during April in the even semester of the academic year 2014/2015. The sample consisted of 22 students from Class X-2 of SMAN 3 Rambah Hilir, selected through purposive sampling. The research instrument was a Physics learning outcomes test. Based on the data obtained from the pretest and posttest, where the students' pretest average score was 40.3, and the posttest average score was 82.4, the magnitude of the influence on students' cognitive learning outcomes in Physics was assessed using the N-gain test, which fell within the high criteria with an average N-gain value of 0.70. The impact of the Learning Cycle 7E instructional model was observed through the achievement of learning objectives. Before the treatment, only 2 out of 15 learning objectives were achieved by students, with a classical mastery level of 13.3%. However, after applying the Learning Cycle 7E instructional model, 13 out of 15 learning objectives were achieved, with a classical mastery level of 86.7%. This result indicates a significant influence of the Learning Cycle 7E instructional model. Based on the research findings, there is an influence on students' cognitive learning outcomes in Physics when using the Learning Cycle 7E instructional model.